Are There Differences in Perception of Predictors of Satisfaction with Work Among Pharmaceutical Executives? A WarpPLS Multigroup Assessment - Oamen, Theophilus Ehidiamen; Ihekoronye, Maduabuchi Romanus (Universitas Negeri Semarang, 2022)
Pharmaceutical sales executives are an essential human resource workforce in medicine supply. These executives come from diverse demographic groupings, which may influence their perceptions and feelings about work engagement (WE) and employer responsiveness (EPR), and consequently influence satisfaction with work (SW). The study aimed to evaluate group differences in the hypothesized influence of WE and EPR on SW. An online questionnaire was administered to a random sample of 369 pharmaceutical executives in Nigeria. Composite-based partial least squares structural equation modeling (PLS-SEM) in WarpPLS software provided the multigroup analysis framework to investigate these hypothesized differences at p<0.05. The overall model revealed adequate model fit and quality with high predictive relevance. WE positively influenced EPR (β=0.592, p<0.001, strong effect ƒ²=0.350) and SW (β=0.519, p<0.001, moderate effect ƒ²=0.298). EPR positively influenced SW (β=0.101, p=0.025, small effect ƒ²=0.041). Non-pharmacist respondents compared to pharmacists had a higher path coefficient in WE influencing SW (β=0.564 vs. β=0.359, p=0.035). Group differences in gender and type of pharmaceutical company were not significant. Participants were more concerned about optimal work situations than having positive or negative feelings about work. The study suggests that non-pharmacist executives show greater adaptability and higher engagement with work, and hence were better satisfied at work.